R-BASED BIBLIOMETRIC ANALYSIS OF TECHNOSTRESS RESEARCH - Temur, Mert; Can, Esin; Yurtseven, Huseyin Ridvan (ESCOLA SUPERIOR DOM HELDER CAMARA, 2026)
The study aims to create a map by presenting analyses of leading researchers in the field, other authors collaborating with these researchers, journals with the highest number and quality of publications, the most frequently used words, the thematic structure of the field, leading countries, and other countries collaborating with these countries. Within this scope, a total of 1,297 English academic publications in the Web of Science database were analysed using the Bibliometrix and Biblioshiny packages in the R programming language. Riedl, Tarafdar, and Maier are leading researchers in the technostress literature. The analysis identified three main theoretical areas. These areas are: information systems and stress theory, technology acceptance and adaptation models, and organisational psychology. Popular topics that will be important for future work in the field are techno-eustress (positive stress from technology) and technodistress (negative stress from technology). The United States, China, and Germany are the countries that contribute most to the field through their international collaborations. Unlike other bibliometric studies that examine technostress more broadly as part of technology-induced stress research, this study focuses solely on the concept of technostress and presents different results for its conceptual structure, which is the most important reason for the uniqueness of this study.
Keywords: Bibliometric Analysis; R-Based Analysis; Technostress; ROLE STRESS; PERFORMANCE; CREATORS; USERS; Government & Law